2002
DOI: 10.1902/jop.2002.73.4.423
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Comparison of a Bovine‐Derived Xenograft Used Alone and in Combination With Enamel Matrix Derivative for the Treatment of Periodontal Osseous Defects in Humans

Abstract: In summary, both the particulate anorganic cancellous bovine-derived bone xenograft used alone and in combination with enamel matrix derivative are effective for the treatment of human intrabony periodontal lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
83
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 53 publications
9
83
2
2
Order By: Relevance
“…Despite these in vitro results, there remains a variety of mixed results over the clinical efficacy of combining Emdogain® with a bone grafting material for clinical use. While some clinical trials have demonstrated that the combination provides additional regeneration, others have failed to show any additional benefit when compared to bone grafting material used alone or Emdogain® used alone [9,12,14,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these in vitro results, there remains a variety of mixed results over the clinical efficacy of combining Emdogain® with a bone grafting material for clinical use. While some clinical trials have demonstrated that the combination provides additional regeneration, others have failed to show any additional benefit when compared to bone grafting material used alone or Emdogain® used alone [9,12,14,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Study that was included in the meta-analysis regarding the treatment with GTR. Study that was included in the meta-analysis regarding the treatment with EMD combined with GTR.e Study that was included in the meta-analysis regarding the treatment with EMD combined with BDX.f Study that was included in the meta-analysis regarding the treatment with BDX alone.xenograft (BDX) (Lekovic et al, 2000(Lekovic et al, , 2001aCamargo et al, 2001;Scheyer et al, 2002;Sculean et al, 2002cSculean et al, , 2003a VelasquezPlata et al, 2002), alloplastic synthetic bone graft (BG) (Sculean et al, 2002b), and demineralized or mineralized freeze-dried bone allografts (DFDBA/FDBA) (Rosen and Reynolds, 2002 Camargo et al, 2001). Similar results were obtained when EMD or autologous fibrinogen/fibronectin system (AFFS) was used in combination with BDX (Lekovic et al, 2001b).…”
mentioning
confidence: 99%
“…However, a recent study comparing the combination of EMD and a bioactive glass to EMD alone failed to show any significant differences between the 2 groups [125] . Furthermore, clinical studies comparing treatment with a combination of EMD and a bone graft/bone substitute to bone graft/bone substitute alone did not demonstrate any advantage of the combination approach [126][127][128] . Thus, it may be speculated that the type of the bone graft/bone substitute and the volume and configuration of the defects are also important factors which might influence the clinical outcomes.…”
Section: Combination Therapies In Intrabony Defectsmentioning
confidence: 95%